Short-term high-fat and high-carb diet effects on glucose metabolism and hedonic regulation in young healthy men - Pointke, Marcel; Strenge, Frank; Piotrowski, Dawid; Matteikat, Anika; Meyhöfer, Svenja; Meyhöfer, Sebastian M.; Chamorro, Rodrigo; Wilms, Britta (Frontiers in Nutrition, 2024)
Background: Daily dietary intake of macronutrients and energy is closely associated with long-term metabolic health outcomes, but whether 24-hour nutritional intervention under isocaloric conditions leads to changes in metabolism remains unclear. Moreover, the short-term effect of diets with different macronutrient composition on hedonic appetite regulation is less clear.Methods: This study examined the impact of an acute high-fat (F+) and high-carbohydrate (C+) diet on glucose metabolism and hedonic regulation of food intake in young healthy men under controlled conditions. Using a cross-over design, 19 male participants received a one-day isocaloric diet with different macronutrient composition (F+ = 11% carbohydrates, 74% fat; C+ = 79% carbohydrates, 6% fat) compared to a control diet (CON = 55% carbohydrates, 30% fat). Protein content was set at 15% of energy in all diets. The feeling of hunger, as well as 'liking' and 'wanting' for foods, was assessed through visual analogue scales, and blood samples for glucose, insulin, and cortisol levels were assessed repeatedly during the experimental day. An intravenous glucose tolerance test was conducted the next morning.Results: Postprandial glucose and insulin levels were lowest in F+ over the 24 hours. Except for dinner, the CON diet showed the highest mean values in glucose. F+ diet improved insulin resistance, lowering Homeostatis Model Assessment Insulin Resistance (HOMA-IR) values. Changes in hedonic regulation of food intake were not observed during the intervention between the diets, except for higher feelings of satiety under the CON diet.